Income Influence in Financial Inclusion: A Multivariate Analysis with Evidence from Central America - López Flores, Walter Jeremías (International Journal of Economics and Financial Issues, 2025)
Financial inclusion is a process that ensures ease of access, availability and usage of the formal financial system for all members of an economy, contributing to economic growth, poverty reduction and lower income inequality; nevertheless, there is a gap between developed countries with respect to developing economies that need to be addressed; besides, studies so far have not centered their attention in Central America. So, the purpose of this research was to determine if income has influence on the financial inclusion of the six countries of such region, through a multivariate analysis of indicators for the main formal financial services: payments, savings and credit through account and credit card ownership and access to formal loans indicators obtained from the Global Findex Database to build a one-way MANOVA model with country income level as a group factor. Results showed that there was a statistically significant difference between the country’s income group on the combined dependent variables: F(1,22) = 7.61, P = 0.0014, and that multivariate financial inclusion was higher in upper-middle income countries than in the lower-middle analyzed, recommending policy-makers to implement public policies that increase their country’s income in order to improve financial inclusion of their population.